The recent dynamics of the disintegrated real estate transfer tax in the EU - MacGregor Pelikánová, Radka; Jánošíková, Petra (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
An important instrument of the fiscal policy is the real estate transfer tax. The approach of EU member states to it has been growing different and departing from the USA model. The comparative study of these heterogeneously different approaches presented in the article is illustrative. The real estate transfer tax system does not belong to the conferred competencies, but a touch of harmonization for states struggling with it, such as the Czech Republic, could help. Hence, the hypotheses to be confirmed or rejected are: (i) real estate transfer tax is inherently particular and harmonization resistant and (ii) real estate transfer tax is not indispensable per se. These hypotheses are addressed while using scientific methods and national statistics. The conclusions confirm both hypotheses and offer thoughts and issues for further research on the (in)capacity of the EU harmonization of the real estate transfer tax and on the (in)effectiveness of the real estate tax, as such
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 482, s. 169-186
Keywords: European Union; Europe 2020; harmonization; real estate transfer tax; Unia Europejska; Europa 2020; harmonizacja; podatek od przeniesienia nieruchomości